To improve the technology of obtaining polymer composite materials on the basis of fillers that provide special properties. (Texas Journal of Multidisciplinary Studies, 2021)
This article is written about the fact that by adding special property fillers to the polymer composition materials, which are obtained on the basis of thermoplastic polymers, they change their properties, obtain such important properties as liquefaction, melting and thermal conductivity